"Narrative dandyism": the theology of creation in the French decadent-dandyist novel 1845-1907 - Burton, T (2017)
This thesis explores how selected "decadent-dandyist" writers of late 19th century France at once exemplify and subvert the self's act of shaping and imprinting its own selfhood upon the world: a model in which an autonomous, discrete artist-self freely creates, and in which both reader/audience and artistic "subjects" are treated as raw canvas and denied agency of their own. Storytellers like Barbey D'Aurevilly, Villiers de l'Isle-Adam, J. K. Huysmans, and Remy de Gourmont create not only hyper-artificial, cloistered, "auto-telic" (to use Charles Taylor's term) textual worlds (e.g. Huysmans' theïbade raffinée) but also hyper-artificial selves: presenting themselves and their often autobiographical protagonists as dandy-artists for whom artistic creation is an extension of self-creation. Central to this thesis is the 19th century figure of the dandy – he who, to quote D'Aurevilly, "[causes] surprise in others, and [has] the proud satisfaction of never showing any oneself." Appropriating the divine power of self-fashioning, the dandy transforms the chaos of existence into a clear narrative over which he alone exerts control, denying that he himself is subject to the control of the world. In my thesis, I first explore the cultural and economic roots of this understanding of the autonomous dandyist-artist in the light of wider tensions in 19th century Paris. I then explore selected "decadent-dandyist" texts through close reading, focusing on the theological implications of our authors’ treatment of narrative, character, setting, and language: showing how our writers cast doubt on both the possibility and morality "autonomous" creation on theological grounds. Finally, I ask how constructive theologians might learn from our authors’ condemnation of "dandyist" storytelling to create a new Christian aesthetics for the novel: proposing elements of an alternate, "kenotic" novel, in which self-projection gives way to "self-giving", a model based not on power and ego but rather on love.